Relation of baseline plasma MMP-1 levels to long-term all-cause mortality in patients with known or suspected coronary artery disease referred for coronary angiography. Issue 1 (March 2015) - Cavusoglu, Erdal; Marmur, Jonathan D.; Hegde, Sudhanva; Yanamadala, Sunitha; Batuman, Olcay A.; Chopra, Vineet; Ay, Gonca; Eng, Calvin
Abstract Objectives To investigate the long-term prognostic significance of baseline plasma MMP-1 levels in a group of well-characterized male patients with known or suspected coronary artery disease, including those presenting with acute coronary syndrome. Background MMP-1 is an interstitial collagenase that is considered the primary enzyme responsible for collagen degradation. In addition, MMP-1 can lead to platelet activation through the PAR1 pathway that is independent of thrombin. Methods Baseline plasma MMP-1 levels were measured in 364 male patients who were referred for coronary angiography and followed prospectively for five years for the development of all-cause mortality. Results After adjustment for a variety of baseline clinical, angiographic and laboratory parameters, baseline plasma MMP-1 levels (analyzed as a continuous variable) were an independent predictor of all-cause mortality at 5 years (HR, 1.49; 95% CI, 1.23–1.80; P < 0.0001). Furthermore, in 3 additional multivariate models that included a wide variety of contemporary biomarkers with established prognostic efficacy (i.e., ST2, GDF-15, Cystatin C, hs-CRP, Myeloperoxidase, NT-proBNP, TIMP-1, Adiponectin, RDW, hemoglobin, and Erythropoietin), MMP-1 remained an independent predictor of all-cause mortality at 5 years. Similar results were obtained when the analyses were restricted to the subpopulation of patients presenting with acute coronary syndrome. Conclusions Elevated levels of MMP-1 are associated with an increased risk of long-term all-cause mortality in patients with known or suspected coronary disease that is independent of a variety of clinical, angiographic, and laboratory variables, including a whole host of contemporary biomarkers with established prognostic efficacy representing multiple different pathophysiologic processes.